The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1159/000016476
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nail Varnish on the Remineralization of Enamel Single Sections Assessed by Microradiography and Confocal Laser Scanning Microscopy

Abstract: Single–section techniques are attractive in enamel de– and remineralization investigations because they allow longitudinal studies in which mineral changes can be assessed by microradiography (TMR). Nail varnish (NV) is in general applied to coat the cut thin–section sides. The aims of this study were to investigate: (1) NV penetration depth in cut surfaces of demineralized enamel, (2) the influence of NV on cut surfaces of demineralized enamel on TMR, (3) the influence of NV penetration on a following reminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Using the thin section technique mentioned [Iijima et al, 1998] mineral changes with time were assessed. The experimental flow diagram is presented in figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the thin section technique mentioned [Iijima et al, 1998] mineral changes with time were assessed. The experimental flow diagram is presented in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…According to Iijima et al [1998], no difference in remineralization efficacy between lesions in bulk samples and lesions in thin sections clamped in a polymethylmethacrylate (PMMA) holder exists. This indicates that by using single sections one can also conveniently and longitudinally investigate the remineralization of in vivo formed WS.…”
mentioning
confidence: 99%
“…To overcome this disadvantage, some researchers used a 'single thin section technique', where incipient lesion is artifi cially produced in the enamel section with a thickness of approx. 100 μm and monitored by TMR analysis 6) , to study the longitudinal mineral change by applying TMR method. However, the section of specimen for this method was fragile.…”
Section: Introductionmentioning
confidence: 99%
“…Dowker et al reported the development of subsurface enamel lesions using micro-CT 5) . Huang et al showed mineral density profi le of enamel white spot lesions using micro-CT 6) . However, they did not investigate longitudinal change in remineralization or longitudinal process of mineral change probably due to diffi culty with accurate alignment of the 3D images.…”
Section: Introductionmentioning
confidence: 99%
“…Crucial to this technique is the durable and impenetrable coating of all surfaces with the exception of a narrow surface window. For this purpose nail varnish has been used for enamel or dentin [Creanor et al, 1986;Wefel and Jensen, 1992;Inaba et al, 1995], and also plastic sheets, epoxy resin or light-curing resin for enamel [Mellberg et al, 1986;Iijima et al, 1998;Exterkate et al, 1993;Tanaka et al, 1993]. Since dentin sections are likely to dehydrate or absorb water, we chose embedding in bonding agent rather than nail varnish.…”
Section: Discussionmentioning
confidence: 99%